2014
DOI: 10.1177/0194599814520685
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Reconstruction of Surgically Created Skull Base Defects: A Systematic Review

Abstract: Based on level 4 evidence, in cases of low-flow intraoperative CSF leaks, skull base reconstruction with multilayered free grafts and synthetic materials offers similar outcomes to vascularized flaps. In cases of high-flow intraoperative CSF leaks, pedicled vascularized flaps appear to be superior. Location of the defect does not seem to be a significant factor in determining successful closure, with the exception of clival defects. In all other sites, good closure may be achieved by multiple reconstructive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 35 publications
7
163
1
6
Order By: Relevance
“…3,13 In the review of 38 studies by Harvey et al, 609 patients with large dural defects were identified. From this cohort, 326 underwent free graft reconstruction while 283 underwent vascularized reconstruction, resulting in a statistically significant difference in the rate of CSF leak of 15.6% (51 of 326) and 6.7% (19 of 283) for free graft and vascularized reconstruction, respectively.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 In the review of 38 studies by Harvey et al, 609 patients with large dural defects were identified. From this cohort, 326 underwent free graft reconstruction while 283 underwent vascularized reconstruction, resulting in a statistically significant difference in the rate of CSF leak of 15.6% (51 of 326) and 6.7% (19 of 283) for free graft and vascularized reconstruction, respectively.…”
Section: 13mentioning
confidence: 99%
“…However, cases with high flow rates revealed improved outcomes with vascularized repairs as leak rates of 82% and 94% were found with free grafts/synthetic materials and vascularized repairs, respectively. 13 The immense versatility of the NSF and the ability to cover a reconstructive area averaging 17.12 cm 2 as delineated by anatomical and radiographic studies has led to its broad use in skull base reconstruction. 10 Moreover, CSF leak rates of 5.7% when used for skull base repair in the setting of high intraoperative CSF flow have been reported.…”
Section: 13mentioning
confidence: 99%
“…Similarly to our technique, their reconstruction begins with the placement of the fascia lata graft in an inlay-outlay fashion, and the reconstruction is supported by a nasoseptal flap. The vascularized nasoseptal flaps have quickly become the workhorse for the repair of skull base defects following endoscopic surgery, with a postoperative success rate of 94% in high-flow CSF leaks [13]. However, nasoseptal flaps present some problems, including the resulting large anterior mucosal defect, which can result in crusting and possible nasal valve stenosis as well as olfactory and mucociliary dysfunction [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, nasoseptal flaps present some problems, including the resulting large anterior mucosal defect, which can result in crusting and possible nasal valve stenosis as well as olfactory and mucociliary dysfunction [14]. On the other hand, multilayered closure with free grafts, such as fascia lata and fat, achieves a success rate of 82% even in high-flow CSF leaks [13]. In this series we successfully closed 15 high-flow CSF leaks and 2 large defects (>30 mm) with our multilayered free graft technique.…”
Section: Discussionmentioning
confidence: 99%
“…Many different techniques have been proposed to repair dural and skull base defects, with success rates ranging from 83% to 95% 4,5 . Recent review articles 6,7 reported 89–92% success for endoscopic repair of skull base defects and identified a potential benefit for vascularized pedicled grafts for large defects or those located in high-flow areas.…”
Section: Introductionmentioning
confidence: 99%